Mechanisms of radiation-induced segregation in CrFeCoNi-based single-phase concentrated solid solution alloys. (March 2017) - He, Mo-Rigen; Wang, Shuai; Shi, Shi; Jin, Ke; Bei, Hongbin; Yasuda, Kazuhiro; Matsumura, Syo; Higashida, Kenji; Robertson, Ian M.
Abstract: Single-phase concentrated solid solution alloys have attracted wide interest due to their superior mechanical properties and enhanced radiation tolerance, which make them promising candidates for the structural applications in next-generation nuclear reactors. However, little has been understood about the intrinsic stability of their as-synthesized, high-entropy configurations against radiation damage. Here we report the element segregation in CrFeCoNi, CrFeCoNiMn, and CrFeCoNiPd equiatomic alloys when subjected to 1250 kV electron irradiations at 400 °C up to a damage level of 1 displacement per atom. Cr/Fe/Mn/Pd can deplete and Co/Ni can accumulate at radiation-induced dislocation loops, while the actively segregating elements are alloy-specific. Moreover, electron-irradiated matrix of CrFeCoNiMn and CrFeCoNiPd shows L10 (NiMn)-type ordering decomposition and <001>-oriented spinodal decomposition between Co/Ni and Pd, respectively. These findings are rationalized based on the atomic size difference and enthalpy of mixing between the alloying elements, and identify a new important requirement to the design of radiation-tolerant alloys through modification of the composition. Graphical abstract: Image 1